Developmental Trajectories of Early Life Stress and Trauma: A Narrative Review on Neurobiological Aspects Beyond Stress System Dysregulation - Agorastos, Agorastos; Pervanidou, Panagiota; Chrousos, George P.; Baker, Dewleen G. (Frontiers in Psychiatry, 2019)
Εarly life stressors are highly prevalent in the general population and constitute a major public health problem. Prolonged psychoneurobiological alterations as sequelae of early life stress (ELS) could represent a developmental risk factor and mediate risk for disease in adulthood, leading to increased physical and mental morbidity in later life. ELS during critical periods of brain development with elevated neuroplasticity could exert a programming effect on particular neuronal and molecular networks related to the stress response and lead to enduring hyper- or hypo-activation of the stress system, associated with adult hypothalamic-pituitary-adrenal axis and glucocorticoid signalling dysregulation. In addition, alterations in emotional and autonomic reactivity, circadian rhythm disruption, functional and structural changes in the CNS, as well as immune and metabolic dysregulation have been lately identified as important risk factors for the development of a chronically impaired homeostatic balance after ELS. The diverse human genetic background and the later engraved epigenetic modifications through stress-related gene expression could interact with these alterations and explain inter-individual variation in vulnerability or resilience to stress. This paper reviews evidence from mainly human research on the most acknowledged neurobiological allostatic trajectories exerting enduring adverse effects of ELS even decades later. Future studies should focus on prospective investigation of putative mediators and their temporal sequence and interactions, while taking into account the potentially delayed time-frame for the expression of their effects. Screening strategies for ELS need therefore to be improved to better identify an individual’s risk for disease development and help prevention and treatment responses.